An Empirical Study on Application of Altman Original Bankruptcy Forecasting Model in Sri Lankan Companies - Velnampy, T. (My University, 2006)
Altman original bankruptcy forecasting model is the first developed model to identify the financial sound or bankruptcy of an organization. Following this model several models are developed for the same purpose. But this model is still accepted to test the financial sound and at the same time, we are aware of no research in the same discipline in Sri Lankan contex. Hence this model is selected to examine the bankruptcy of the companies. The financial institutions and commercial banks are interested to know whether a particular company will be in a position to repay its debts. Here the firm’s ability to repay its debts should be predicted. In this paper, financially sound or bankruptcy of the companies is examined by using Altman’s original bankruptcy forecasting model with the samples of 25 quoted companies in Sri Lanka. Five years data during the periods of 1999/2000-2003/2004 are taken for the study. Major finding of the study is that only four companies, out of 25 Companies, are in the position of financially sound.
Keywords: Bankruptcy; Financial position; Performance; Profitability; Predicting; Ratios